2017
DOI: 10.15587/2519-4852.2017.119279
|View full text |Cite
|
Sign up to set email alerts
|

Cycloalkanecarbaldehydes in synthesis of novel 1,2-benzoxathiin-4(3H)-on 2,2-dioxide derivatives and study of the antimicrobial activity of synthesized compounds

Abstract: Метою даної роботи було дослідження взаємодії циклоалканкарбальдегідів, 1,2-бензоксатіїн-4(3Н)-он 2,2-діоксиду та метиленактивних нітрилів та вивчення антимікробних властивостей одержаних сполук. Методи: Як вихідні речовини були використані циклоалканкарбальдегіди, 1,2-бензоксатіїн-4(3Н)-он 2,2діоксид та метиленактивні нітрили. В ході дослідження застосовувались методи органічного синтезу. Структуру синтезованих сполук було підтверджено елементним аналізом та 1 Н ЯМР-спектроскопією. Антимікробну активність вим… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The antimicrobial activity of the compounds tested was moderate and more pronounced against grampositive bacteria than gram-negative ones and fungi [49][50][51][52].…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The antimicrobial activity of the compounds tested was moderate and more pronounced against grampositive bacteria than gram-negative ones and fungi [49][50][51][52].…”
Section: Resultsmentioning
confidence: 98%
“…Another example of the 1,2-benzoxathiin-4(3H)one 2,2-dioxide carbonyl group modification is the preparation of enamines. The authors [28] found conditions for the interaction of compound 1 with piperidine (51), which led to the formation of 4-(1-piperidinyl)benzoxathiine 2,2-dioxide (52) with the yield of 76 % (Scheme 16). Considering the fact that in medicinal chemistry sultons are known because of their anti-inflammatory effects [40] the authors of the current work studied and revealed the anti-inflammatory properties of 52, which reduced carrageenan edema when administered intraperitoneally to rats (100 mg/kg).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation